Assessment of Children's Oral Health-Related Knowledge and Self-Efficacy in Expectant Mothers of Najran, Saudi Arabia - Siraj Dain Ali Ahmed Khan; Musleh Al-Garni; Mishary Nasser Al Khurim; Eidan Safir Alkhathami; Bader Hussain Al Sayhab; Farhaan Mahdi Al Salaah; Khalaf Nasser Al Qshanin (Association of Support to Oral Health Research (APESB), 2022)
Objective: To assess the knowledge of pregnant women regarding their child's oral health. Material and Methods:  A questionnaire was developed and the 1st section comprised sociodemographic variables. The second section contained questions about the eruption of teeth, fluoride importance, cariogenic food, and dental visits. The questionnaire was shared electronically via a link to the receptionist of the gynaecologist at different health centres of Najran to be filled by expectant mothers. The convenient sampling method was used to collect the responses. Data were presented using descriptive statistics. Results: A total of 572 pregnant women participated in this survey. Three hundred and fifteen (55.1%) knew that 1st primary tooth erupts at the age of 6 months. The majority of the respondents (n=332) agreed that toothbrushes and toothpaste could be used to clean a child's teeth; only 5.4%, 10%, and 24.5% preferred miswak, mouthwash, and toothbrush, respectively. Participants were well familiar with cariogenic food and occasionally allowed their children to take it. They have enough knowledge about fluoride toothpaste, but they were not familiar with the benefits of fluoride varnish. Almost 50% of the respondents agreed that the child should visit the dentist within six months, and 27.4% said they should visit the dentist whenever there is a problem. Conclusion:  Almost 50% of participants showed a positive attitude towards most questions. However, there is a need to improve their  behaviour and knowledge about many aspects of dental care.